Brexit and academia: a satyr play where exit prevails voice. (2nd January 2021) - Baumbach, Sibylle; Maurer, Andreas
ABSTRACT: This introduction to the special issue Brexit and Academia sketches some of the key challenges for academia that emerged from Brexit. Based on a brief overview of the current state of the withdrawal and the trade agreements, we reflect upon the consequences of Brexit on transnational research, academic mobility, and research funding. We discuss the role and function of Euroscepticism for understanding the United Kingdom's slow but constant move towards exiting the Union. We further outline the key function of Euroscepticism for explaining the formation of an imagined community of 'Brexiteers' in fostering the rise of an 'island mentality.' The introduction closes by considering potentially productive effects of a crisis such as Brexit, which has opened up new areas for research across various disciplines.